Would you rather be a hero (unsung) or a celebrity? - Jeremy Grabbe; Bethany Jurs; Lynn McCutcheon; Scott Peterson; Emilia Flint (Academia Mental Health & Well-Being)
This study aimed to provide further validation for a brief measure of the widely used Celebrity Attitude Scale (CAS) in an American sample. We administered a brief version of a measure of admiration for one’s favorite celebrity, the Celebrity Attitude Scale-Brief (CAS-B), along with brief measures of either the desire to be a hero/heroine or the desire to be a celebrity, to 159 randomly assigned college students. Our first hypothesis was that the “desire to be a celebrity” would be stronger than the “desire to be a hero/heroine”. We also hypothesized that there would be a positive correlation between scores on the CAS-B and scores on a measure of the desire to be a celebrity, as well as between CAS-B scores and the desire to be a hero. Results showed that the desire to be a hero was stronger than the desire to be a celebrity. We did find the hypothesized correlation between CAS-B scores and the desire to be a celebrity, but CAS-B scores were not significantly related to the desire to be a hero. The discussion centers on reasons for the unexpected results of our first hypothesis and the validation of the CAS-B.